Synthesis and odour evaluation of tricyclic ether derivatives containing a cis‐1, 2‐dimethyl norbornane moiety. (11th December 2014) - Clinet, Adrien; Chaignaud, Mathilde; Clinet, Jean‐Claude; Dunach, Elisabet
Abstract Series of differently substituted tricyclic ethers have been synthesized on a multi‐gramme scale from a common cis‐1, 2‐dimethyl norborane structure. Olfactory evaluation of these compounds is presented and reveals mainly woody aspects as the predominant notes. Copyright © 2014 John Wiley & Sons, Ltd.